CLINICAL AND LABORATORY FEATURES OF ESSENTIAL THROMBOCYTOSIS AND PRIMARY MYELOFIBROSIS DEPENDING ON JAK2 AND CALR1 MUTATION STATUS - E. G. lisina; N. T. Siordiya; P. A. Butylin; A. A. Silyutina; N. M. Matyukhina; O. M. Senderova; E. S. Fokina; V. A. Ovsepyan; E. G. Lomaia; A. Yu. Zaritskiy (Онкогематология, 2017)
Introduction. JAK2V617F mutation is detected in approximately 50 % of patients with essential thrombocytosis (ET) and primary myelofibrosis (PMF). In 2013 most of the JAK2 negative patients showed mutations in the CALR gene. Diagnostic value of JAK2 and CALR mutations is high, but their prognostic significance is not sufficiently clear. Data on impact of JAK2 and CALR mutational status on thrombotic complications in ET and myelofibrosis patients are contradictory.The aim of the study was to identify clinical and laboratory features in patients with ET and PMF in accordance with the mutational status of JAK2V617F and CALR gene.Materials and methods. Patients treated in Almazov National Medical Research Center (St. Petersburg), Chuvash Republican Clinical Hospital (Cheboksary), Irkutsk Regional Clinical Hospital (Irkutsk),  Kirov Research Institute of Hematology and Blood Transfusion (Kirov) was included in the retrospective study. CALR mutation (1 and 2 types), MPL W515L/K and JAK2V617F mutation were detected in peripheral blood cells.Results. We identified that 21 % (n = 16) of ET patients had thrombotic complications, and they occurred more often among JAK2V617F positive patients (p <0.05). The median of hemoglobin level in PMF was the lowest in the group of triple negative patients. The level of leukocytes in PMF was higher in the group of triple negative patients than in the group with mutated CALR (p = 0.014).Conclusion. JAK2V617F mutation in ET patients was associated with a high risk of thrombosis. Patients with CALR mutations may have a favorable prognosis regarding to thrombotic complications. Some laboratory features of CALR mutations in ET and PMF patients have been revealed.